Study on polarisation ratio for X-band using dual-polarisation Terra-SAR X image - Shao, Weizeng; Lehner, Susanne; Guan, Changlong (International Geoscience and Remote Sensing Symposium (IGARSS), 2012)
In this study, we present the analysis of measurements of normalized radar cross section (NRCS) and the polarisation ratio (PR) in dual-polarisation TerraSAR-X (TS-X) images. Based on two PR functions proposed for C-band SAR (denoted as the Thompson model and Elfouhaily model respectively) and the relationship between NRCS and incidence angle for X-band (it is called X-PR), three PR models are tuned using 45 dual-polarisation TS-X images. The PR is found to be dependent of the incidence angle and VV-polarisation NRCS is larger than HH-polarisation NRCS when the incidence angle is larger than 23°. A total of 20 HH-polarisation TS-X images are analyzed for retrieving the wind field using three PR models and XMOD algorithm together. The results are compared to QuikSCAT data and buoy measurements for validation. The root-mean-square error (RMSE) of wind speed is 2.34m/s, 2.16m/s and 1.99m/s with a correlation of 0.82, 0.87 and 0.88 by using Thompson model, Elfouhaily model and X-PR model respectively for the cases. © 2012 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: polarisation ratio; TerraSAR-X; wind field; XMOD